Pencegahan Keruntuhan Progresif pada Struktur Jembatan Tinjomoyo dari Analisis Hidrologi dan Geoteknik - Udayanto, Nugroho Sungkono; Agus Sulaeman; Roni Farfian (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2024)
This study aims to analyze measures to prevent progressive collapse of the Tinjomoyo Bridge in Semarang through hydrological and geotechnical approaches. The research employs a quantitative method with a descriptive approach to evaluate issues encountered in the field. The study includes an analysis of the impact of adding crib structures on riverbank slopes to mitigate scouring caused by water flow and redesigning the bridge pier foundation structure based on soil investigation data and loading conditions. Hydrological analysis indicates that a downstream weir slope of 20% effectively directs water flow to prevent damage to the slopes and bridge piers. Simulations using Plaxis 8.2 reveal that adding crib structures to the riverbank reduces longitudinal displacement by 269.07 mm. Furthermore, the structural safety factor increases from 10.774 (initial condition) to 12.024 (engineered condition). From a geotechnical perspective, redesigning the pier foundation using bored piles with a diameter of 1 meter and 12 pile groups effectively supports the applied loads. Based on the analysis, the proposed crib and foundation design are recommended as solutions to prevent progressive collapse of the Tinjomoyo Bridge. This solution is expected to provide long-term safety and stability for the bridge structure.